Treatment of post-resuscitation cicatricial tracheal stenosis after suffering severe COVID-19 associated pneumonia: A report of 11 cases. (2022) - Topolnitskiy, Evgeniy; Chekalkin, Timofey; Marchenko, Ekaterina; Volinsky, Alex
Abstract: Objective: Despite the full range of anti-epidemic measures, the rapidly mutating SARS-CoV-2 continues to spread worldwide, causing respiratory and pulmonary pathologies. So far, there are no generally accepted clinical guidelines for treating post-resuscitation cicatricial tracheal stenosis (CTS) after COVID-19 associated pneumonia. This study sought to evaluate the clinical outcomes of surgical treatment and perioperative management of patients who developed CTS. Methods: A cohort of eleven working-age patients (eight women and three men) with CTS were treated surgically after undergoing invasive artificial ventilation ranging from 5 to 130 days. Along with scarring changes in the tracheal wall, tracheomalacia was noted in five (55.6%) individuals. Circumferential tracheal resection (CTR) with subsequent anastomosis, tracheolaryngeal reconstruction, and endoscopic methods were modalities used to restore airway patency. In cases of CTR combined with tracheoesophageal fistula (TEF), CTR was performed with dissection of the pathological stoma. Results: In 80% of the cases, CTS was located at the larynx and cervical trachea level. All patients managed to restore adequate breathing through their natural airways with preserved vocal function. No lethal outcomes were observed in the post-op period. Patient outcomes after CTR were considered excellent in nine patients who continued an active lifestyle and went straight to work. One patient, after laryngotracheoplasty and tracheal stenting, is at the final stage of treatment. Conclusions: These patients are at high risk of developing CTS and require dynamic monitoring. CTR allows early rehabilitation of patients with the best functional outcome. If CTR is contraindicated, laryngotracheoplasty also allows adequate debridement of the tracheobronchial tree and respiratory support.